2021
DOI: 10.1016/j.arth.2021.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Patient Engagement in Total Joint Arthroplasty Using Digital Application-Based Technology

Abstract: Background: Digital patient engagement has been suggested as a mean to increase patient activation and patient satisfaction after total joint arthroplasty. The purpose of this study was to assess patient engagement with application-based educational tools and to explore what content was most useful to patients in the perioperative period surrounding total hip arthroplasty (THA) and total knee arthroplasty (TKA), respectively. Methods: Patients undergoing THA and TKA between October 2017 and January 2020 were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
(30 reference statements)
1
18
0
4
Order By: Relevance
“…7 Preoperative caregiver education interventions using audiovisual aids similar to the orthopaedic total joint population may help address many of these concerns and enable a more timely discharge from the hospital. 23,24 Delayed wheelchair ordering, delivery issues, or poor wheelchair fit proved to be a recurrent barrier to discharge in this study. Complications with obtaining the correct assistive devices for postoperative patients with neurological CCC are directly impacted by interdisciplinary staff member communication involving nursing, physical and occupational therapy, orthopaedic surgery, and case management.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…7 Preoperative caregiver education interventions using audiovisual aids similar to the orthopaedic total joint population may help address many of these concerns and enable a more timely discharge from the hospital. 23,24 Delayed wheelchair ordering, delivery issues, or poor wheelchair fit proved to be a recurrent barrier to discharge in this study. Complications with obtaining the correct assistive devices for postoperative patients with neurological CCC are directly impacted by interdisciplinary staff member communication involving nursing, physical and occupational therapy, orthopaedic surgery, and case management.…”
Section: Discussionmentioning
confidence: 72%
“…Berry and colleagues found that multiple preoperative primary care visits were associated with lower hospital costs and shorter LOS 7. Preoperative caregiver education interventions using audiovisual aids similar to the orthopaedic total joint population may help address many of these concerns and enable a more timely discharge from the hospital 23,24…”
Section: Discussionmentioning
confidence: 99%
“…Overall, previous studies of orthopaedic patient perspectives with smartphone and smartwatch apps agree that the perception of personal benefit, ease of use, and satisfaction with the feedback provided by the technology are crucial to engagement, which was difficult to maintain beyond a relatively short study period, ranging from weeks up to a year. 13,17,18 These findings suggest that the enthusiasm for digital technology we recorded in our study for TKA, and thus the overarching compliance, may decline over time if it does not actively support or facilitate continued patient engagement. Depending on the technology and associated engagement approaches, therefore, challenges for collecting meaningful long-term real-world evidence about orthopaedic implant performance may exist.…”
Section: Discussionmentioning
confidence: 88%
“…Relatively few studies have focused on patient perspectives on using wearables and smartphones for orthopaedic patients, 13,17,18 complicating direct comparisons with our research. Knapp et al 17 studied the use of a smartphone or a web-based app to engage their total hip arthroplasty and TKA patients in their treatment with educational prehabilitation and postsurgery rehabilitation modules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation